2011
DOI: 10.1056/nejmoa1007487
|View full text |Cite
|
Sign up to set email alerts
|

Perilipin Deficiency and Autosomal Dominant Partial Lipodystrophy

Abstract: Perilipin is the most abundant adipocyte-specific protein that coats lipid droplets, and it is required for optimal lipid incorporation and release from the droplet. We identified two heterozygous frameshift mutations in the perilipin gene (PLIN1) in three families with partial lipodystrophy, severe dyslipidemia, and insulin-resistant diabetes. Subcutaneous fat from the patients was characterized by smaller-than-normal adipocytes, macrophage infiltration, and fibrosis. In contrast to wild-type perilipin, mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
192
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 263 publications
(213 citation statements)
references
References 27 publications
5
192
1
1
Order By: Relevance
“…We have recently reported the fact that loss-of-function mutations in two of these LD coat proteins are associated with smaller LDs and lipodystrophy (19,20). We have now also shown that siRNA-mediated PCYT1A knockdown impairs adipogenesis in cultured adipocytes.…”
Section: Resultsmentioning
confidence: 86%
“…We have recently reported the fact that loss-of-function mutations in two of these LD coat proteins are associated with smaller LDs and lipodystrophy (19,20). We have now also shown that siRNA-mediated PCYT1A knockdown impairs adipogenesis in cultured adipocytes.…”
Section: Resultsmentioning
confidence: 86%
“…In adipocytes, lipolytic regulation affects free fatty acid delivery to all other tissues in the whole organism, whereas most other tissues largely regulate lipid stores in a cell-autonomous fashion, an obvious exception being hepatocytes, which can release TAG within lipoproteins. The fact that patients with loss-of-function mutations in perilipin 1, shown to result in elevated basal lipolysis, manifest such severe metabolic consequences including partial lipodystrophy, severe insulin resistance, diabetes, dyslipidaemia, and nonalcoholic fatty liver disease highlights the importance of perilipin 1 in regulating adipocyte lipolysis (22,23). In the fasting state or during exercise, lipolysis is dramatically increased (severalfold) to deliver free fatty acids for oxidative phosphorylation in muscle and other energetically demanding tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Granneman et al (21) later showed that this interaction sequestered ABHD5 from interacting with ATGL whereas they suggested that the interaction between perilipin 2 and ABHD5 was significantly weaker (21). We recently identified lossof-function frameshift PLIN1 mutations in patients with partial lipodystrophy, severe insulin resistance, dyslipidaemia, and nonalcoholic fatty liver disease (22). When expressed in cultured adipocytes, the mutants, which primarily alter the C terminus of perilipin 1, failed to sequester ABHD5 from ATGL or to suppress basal lipolysis (23).…”
mentioning
confidence: 99%
“…Two deletions and one splice site variant, all resulting in frameshifts, have been identified. 10,11 Two of them have been shown to alter physiological functions of perilipin. 12 CIDEC-FPLD5 is an autosomal recessive disorder.…”
Section: Mutational Spectrummentioning
confidence: 99%